Gender Bias in Teaching Evaluations - Friederike Mengel; Jan Sauermann; Ulf Zölitz (Institute of Labor Economics (IZA), 2017)
This paper provides new evidence on gender bias in teaching evaluations. We exploit a quasi-experimental dataset of 19,952 student evaluations of university faculty in a context where students are randomly allocated to female or male instructors. Despite the fact that neither students' grades nor self-study hours are affected by the instructor's gender, we find that women receive systematically lower teaching evaluations than their male colleagues. This bias is driven by male students' evaluations, is larger for mathematical courses and particularly pronounced for junior women. The gender bias in teaching evaluations we document may have direct as well as indirect effects on the career progression of women by affecting junior women's confidence and through the reallocation of instructor resources away from research and towards teaching.
Keywords: J16; J71; I23; J45; 330; gender bias; teaching evaluations; female faculty